Can ICT be Driving Force behind the Acceleration of Small and Medium Enterprise Profitability: Evidence from Nepal - Sigdel, Amit; Mahapatra, Sushanta; Paudel, Udaya Raj; Kunwar, Ramesh (Quest Journal of Management and Social Sciences, 2024)
Background: SMEs are critical to a country's economic development; researchers are increasingly focusing on their adoption and use of information and communication technology. Previous research has revealed that the contribution of ICT to SMEs performance and profitability is not clear or certain. Objective: This study examines the adoption among SMEs in terms of the advanced stage from technology adoption to post-adoption. The mediating impact of performance on profitability is also being investigated. Method: The exploratory research design was chosen as the primary study model in order to find reality. To examine the data quantitatively, descriptive and inferential statistics were used. A convenience sampling with a sample size of 201 SMEs were chosen for the study based on practical experience and adequate ICT knowledge. Result: The study found that ICT usage and profit have a significant link. However, the performance of SMEs does not play a role in moderating the relationship between ICT usage and profitability because our study finds degree of utilization ICT usage doesn’t play any significant role in performance. Conclusion: ICT is still a new concept in SMEs that deserves to be given more attention. Employees and organizations must use ICT, technology system integration, and finally implementation across all functional areas to increase the profitability of SMEs. This study recommends that government should initiate ICT awareness programs in SMEs, provide subsidies and grants for ICT adaptation and use, education sectors should focus on technology skill manpower, and ICT should be used and integrated across all functional areas of SMEs to increase profit. Paper Type: Research Paper Key words: ICT, Small Medium Enterprise, Profitability, Performance JEL Classification: M41, M15, C88, D91, N95, C38